Preparation of Venlafaxine-Antidepressant Drug - POORNA CHANDER, T.; SANTA DEEPTHI, K.; KALYAN CHAKRAVARTHY, A.; MAHESH REDDY, GHANTA (Asian Journal of Chemistry, 2010)
Venlafaxine (1) is an antidepressant and an alternative for tricyclic antidepressants or MAO inhibitor. Its synthesis generally suffers from low yields, tedious workup and high cost. To over-come these drawbacks, a simple, facile, cost effective and friendly process at industrial scale is reported.